2021
DOI: 10.3390/ijms22115629
|View full text |Cite
|
Sign up to set email alerts
|

The Wall-Associated Receptor-Like Kinase TaWAK7D Is Required for Defense Responses to Rhizoctonia cerealis in Wheat

Abstract: Sharp eyespot, caused by necrotrophic fungus Rhizoctonia cerealis, is a serious fungal disease in wheat (Triticum aestivum). Certain wall-associated receptor kinases (WAK) mediate resistance to diseases caused by biotrophic/hemibiotrophic pathogens in several plant species. Yet, none of wheat WAK genes with positive effect on the innate immune responses to R. cerealis has been reported. In this study, we identified a WAK gene TaWAK7D, located on chromosome 7D, and showed its positive regulatory role in the def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…In Arabidopsis, rice, maize, cotton, and wheat, some WAK/WAKL proteins were reported to have an important function in resistance responses to the bacterial or fungal pathogens [ 14 , 15 , 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 ]. In this study, on the basis of the RNA-seq data and qRT-PCR analyses, we identified the wheat-wall-associated kinase gene, TaWAK2A-800, with broad-spectrum resistance against R. cerealis and F. graminearum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, rice, maize, cotton, and wheat, some WAK/WAKL proteins were reported to have an important function in resistance responses to the bacterial or fungal pathogens [ 14 , 15 , 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 ]. In this study, on the basis of the RNA-seq data and qRT-PCR analyses, we identified the wheat-wall-associated kinase gene, TaWAK2A-800, with broad-spectrum resistance against R. cerealis and F. graminearum .…”
Section: Discussionmentioning
confidence: 99%
“…Chitin was suspended in sterile water and used at a final concentration of 100 μg/mL [ 24 ]. Wheat seedlings were sprayed with distilled water (mock), or chitin solution.…”
Section: Methodsmentioning
confidence: 99%
“…WAK-like (WAKL) proteins were similar to WAK proteins in the structure, both of them have the extracellular WAK and Ser/Thr kinase domains, while the EGF domain was specific to WAK proteins [ 7 ]. WAK/WAKLs are the only kind of receptors involved in cell wall signaling, which can directly transfer signals from extracellular to cytoplasm, and they also work in plant cell expansion, metal tolerance, plant disease resistance and response to various plant hormones and abiotic stresses [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all WAK5 family members clustered on the same branch, including Zea, mays ZmWAK5, Sorghum bicolor SbWAK5, Dichanthelium oligosanthes DoWAK5, Hordeum vulgare HvWAK5, Aegilops tauschii AeWAK5, Brachypodium distachyon BdWAK5, and Oryza sativa OsWAK5 . The second branch included Setaria italica SiWAK5, and six previously reported disease resistance-related WAKs of monocots, including Zea, mays ZmWAK-qHSR1 (Zuo et al, 2015 ), ZmWAK-RLK1 ( Htn1 ) (Hurni et al, 2015 ), O. sativa OsWAK-Xa4 (Hu et al, 2017 ), T. aestivum Stb6 (Saintenac et al, 2018 ), TaWAK-7D (Qi et al, 2021 ), and TaWAK6 (Dmochowska-Boguta et al, 2020 ). Meanwhile, T. aestivum TaWAK-6D and other five WAK2 family members were clustered on the third branch, including Setaria viridis Sv WAK2, Oryza brachyantha ObWAK2, H. vulgare HvWAK2, Triticum dicoccoides TdWAK2 , and A. tauschii subsp.…”
Section: Resultsmentioning
confidence: 99%